2015
DOI: 10.1111/aor.12588
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Pulsatile Extracorporeal Membrane Oxygenation on Hemodynamic Energy and Systemic Microcirculation in a Piglet Model of Acute Cardiac Failure

Abstract: The objective of this study was to compare the effects of pulsatile and nonpulsatile extracorporeal membrane oxygenation (ECMO) on hemodynamic energy and systemic microcirculation in an acute cardiac failure model in piglets. Fourteen piglets with a mean body weight of 6.08 ± 0.86 kg were divided into pulsatile (N = 7) and nonpulsatile (N = 7) ECMO groups. The experimental ECMO circuit consisted of a centrifugal pump, a membrane oxygenator, and a pneumatic pulsatile flow generator system developed in‐house. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…A similar trend, albeit not significant, was also shown in the CESAR trial [99]. However, autoregulation of renal microcirculation may deteriorate during non-pulsatile ECMO as shown in an acute cardiac failure model in pigs [105]. Other factors negatively influencing renal function during ECMO treatment may be fluid overload [106] ischaemia/reperfusion injury [107], and circuit-related factors [108,109].…”
Section: Rationalementioning
confidence: 68%
“…A similar trend, albeit not significant, was also shown in the CESAR trial [99]. However, autoregulation of renal microcirculation may deteriorate during non-pulsatile ECMO as shown in an acute cardiac failure model in pigs [105]. Other factors negatively influencing renal function during ECMO treatment may be fluid overload [106] ischaemia/reperfusion injury [107], and circuit-related factors [108,109].…”
Section: Rationalementioning
confidence: 68%
“…A recent study by Itoh et al using a similar model of pulsatile vaECMO but in pigs remaining in ventricular fibrillation for 180 min, showed improved microcirculation parameters and higher hemodynamic energy in the pulsatile vaECMO group compared to continuous flow vaECMO. This may have also acted in favor of a better LVEF recovery in our study .…”
Section: Discussionmentioning
confidence: 77%
“…Pulsatile flow may lower pulmonary artery pressures and cause lower endothelial activation and higher anti‐inflammatory cytokines secretion . Other studies have also suggested that pulsatile extracorporeal flow provides superior end‐organ protection with improved renal function and systemic vascular tone possibly through improved systemic microcirculation . Therefore, in this study, we tested a high pulsatile pressure during CARL and the MAP data demonstrated in Figure show that we were able to provide high pressure CARL compared to the low pressure and nonpulsatile flow CARL.…”
Section: Discussionmentioning
confidence: 82%